Does institutional quality matter in SME financing? Empirical evidence on credit access and investment behavior - Angelia Nirwana Sari, Laras; Setiawati, Liya (Journal Economic Business Innovation, 2025)
Purpose: Therefore, we are motivated to investigate how the quality of institution molds firms financing choices and investment behaviour over administrated external or internal sources of finance.Method: Adopting multivariate regression and moderation analysis, this paper conducted a quantitative research which investigated the association between institutional quality, financing access and investment behavior based on firm-level data.Findings: The findings indicate that the quality of institutions significantly increases the ability to access external finance, whereas institutional inefficiency raises reliance on internal capital. Interaction between external and internal financing further confirms a substitution effect: Firms tend to dynamically adjust their funding structure according to the strength of institutions. The empirical findings also reveal that the role of institutions in shaping tangible investment is all the more vital, stressing governance quality as a pre-requisite for both financial inclusiveness and capital creation.Novelty: This paper combines institutional and financing considerations in a single empirical setting to overcome the poor evidence on how institutional quality jointly determines access to finance and investment behaviour. It offers a new concept lens to explain substitution financing mechanisms in the institutional divergence, Emerging economies.Implications: The results are evidence that institutional reforms, transparency and governance improvement is a key element in the development of financial accessibility and investment growth. Policy makers should encourage institutional effectiveness to promote sustainable economic growth and alleviate firms’ reliance on internal capital sources.